Microglia-Derived Interleukin 23: A Crucial Cytokine in Alzheimer's Disease? - Nitsch, Louisa; Schneider, Linda; Zimmermann, Julian; Müller, Marcus (Frontiers in Neurology, 2021)
Neuronal cell death, amyloid β plaque formation and development of neurofibrillary tangles are among the characteristics of Alzheimer's disease (AD). In addition to neurodegeneration, inflammatory processes such as activation of microglia and astrocytes are crucial in the pathogenesis and progression of AD. Cytokines are essential immune mediators of the immune response in AD. Recent data suggest a role of interleukin 23 (IL-23) and its p40 subunit in the pathogenesis of AD and corresponding animal models, in particular concerning microglia activation and amyloid β plaque formation. Moreover, in animal models, the injection of anti-p40 antibodies resulted in reduced amyloid β plaque formation and improved cognitive performance. Here, we discuss the pathomechanism of IL-23 mediated inflammation and its role in AD.